Delayed facial palsy after cochlear implantation caused by reactivation of Herpesvirus: A case report and review of the literature. Issue 5 (October 2022) - Ishikawa, Yui; Hosoya, Makoto; Kanzaki, Sho; Ogawa, Kaoru
Abstract: Cochlear implantation has many complications; however, delayed facial palsy is relatively rare. In this report, we present the case of a 60-year-old woman with delayed facial palsy after cochlear implantation. Eleven days after the operation, the patient complained of right facial palsy (Yanagihara score 6, House–Brackmann [HB] grade VI). Herpes virus reactivation and local bacterial infection were considered as possible causes of the facial paralysis. A blood test revealed an increase in viral antibody titer, and the patient was diagnosed as having herpes virus reactivation. She was treated with antiviral therapy for the facial palsy until resolution. Slight mouth weakness continued even at 1.5 months (Yanagihara score 34, HB II) but eventually resolved at 3 months (Yanagihara score 40, HB I). Delayed facial palsy is a rare but serious complication that can occur with viral reactivation regardless of the competence of the surgical procedure. Therefore, it is important to inform patients preoperatively regarding the risk of not only immediate but also delayed postoperative facial paralysis.